The Moderating Role of Transformational Leadership on the Relationship Between Perceived External Prestige and Employee Performance - Ardiansyah, Fuad; Sanaba, Hardiman F.; Salu, Lorena Tiku; Budi, Achmad R. S. (Jurnal Sains Psikologi, 2024)
An in-depth exploration of how the dimensions of transformational leadership individually moderate the influence of perceived external prestige on employee performance is still lacking. This research uses a quantitative approach measured by three scales: the transformational leadership perception scale modified from previous research (reliability value of .957), the perceived external prestige scale constructed by revealing aspects of personality, social development, and career training (reliability value of .962), and the employee performance scale modified from previous research (reliability value of .961). The research sample consisted of employees from various agencies, totaling 213 people. Data analysis in this research used moderated regression analysis. The results showed that transformational leadership serves as a moderator that strengthens the influence of perceived external prestige on employee performance, which means that the positive influence of perceived external prestige on employee performance will be more substantial if it is supported by transformational leadership.